2016
DOI: 10.1002/1878-0261.12017
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition in tumor metastasis

Abstract: The Epithelial–Mesenchymal Transition (EMT) is a developmental program that enables stationery epithelial cells to gain the ability to migrate and invade as single cells. Tumor cells reactivate EMT to acquire molecular alterations that enable the partial loss of epithelial features and partial gain of a mesenchymal phenotype. Our understanding of the contribution EMT to tumor invasion, migration, and metastatic outgrowth has evolved over the past decade. In this review, we provide a summary of both historic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
450
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(486 citation statements)
references
References 93 publications
8
450
0
4
Order By: Relevance
“…Moreover, patients with low expression levels of miR-381 exerted high SOX4 protein expression levels. EMT caused tumor metastasis has been well established (20). Even, in general, SOX4 didn't bind to the promoters of EMT markers to regulate their expression (21), but SOX4 has been demonstrated to promote the EMT in lung cancer (22) and prostate cancer (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients with low expression levels of miR-381 exerted high SOX4 protein expression levels. EMT caused tumor metastasis has been well established (20). Even, in general, SOX4 didn't bind to the promoters of EMT markers to regulate their expression (21), but SOX4 has been demonstrated to promote the EMT in lung cancer (22) and prostate cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Even, in general, SOX4 didn't bind to the promoters of EMT markers to regulate their expression (21), but SOX4 has been demonstrated to promote the EMT in lung cancer (22) and prostate cancer (23). Data showed that a SOX4/EZH2 protein complex could be formed to bind to promote serval EMT related transcription factors expression, such as Snail, Zeb, and Twist (20). In order to know whether miR-381/SOX4 axis could regulate the EMT in gastric cancer, we detected three markers of EMT and found that miR-381 overexpression increased the endothelial marker's (E-cadherin) expression whereas inhibited mesenchymal makers' (N-cadherin and vimentin) expression.…”
Section: Discussionmentioning
confidence: 99%
“…SKOV3 (1x10 4 ) and OVCAR3 (5x10 4 ) cells were trypsinized and resuspended in growth medium containing 0.35% agarose (BD Biosciences), and then plated onto a solid layer of 0.7% agarose in growth medium in 6-well plates. Fresh medium (500 µl) was added on alternate days for two weeks.…”
Section: Lentiviral Vector Productionmentioning
confidence: 99%
“…However, the molecular mechanisms underlying the tumor metastasis and chemoresistance in ovarian cancer are not well understood. The epithelial-mesenchymal transition (EMT) contributes to the tumor metastasis and chemoresistance (4). EMT is a biological process accompanied by the loss of cell adherence junctions and apical-basal polarity, and acquisition of the mesenchymal phenotype to increase cell motility and invasiveness (5).…”
Section: Introductionmentioning
confidence: 99%
“…During metastasis, cells invade tissues, migrate through the lymphatic and circulatory systems, travel long distances, and establish in new tissues to form tumors [153]. Although the migration ability of stem cells is repressed after embryonic development, it probably reappears when stem cells or their environments become altered, for example, after tissue injury or under an inflammatory context [162][163][164][165][166]. The activation of developmental programs (e.g., epithelialmesenchymal transition programs) during metastasis can explain why, despite intensive efforts, no genetic mutation has been shown to be required for metastasis [5]; these developmental programs do not require mutations to be activated.…”
Section: The Stem Cell Division Theory Of Cancer Provides a New Framementioning
confidence: 99%